Pelatihan Pembuatan Running Text Sebagai Pengembangan Minat Dan Bakat Siswa SMP - Sukma, Septi Ambar Indraningtia; Bachtiar, Moch. Rizki Agil; Irgiansyah, Ahmad; Septa, Karunia; Herawati, Diva Vita; Prayoga, Aldi; Ahdi, M. Wafiyul (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
ABSTRACT This community service project aims to develop the interest and skills of junior high school students in Kedungbogo Village in the field of technology, particularly in creating and managing running text. The program includes comprehensive training that introduces the participants to the basics of running text technology, including practical skills in designing and implementing it effectively. The training outcome shows an increase in students' technical abilities and their interest in further exploring the field of information technology. Although post-training surveys have not yet been conducted, initial indications show a positive response, with participants beginning to apply the technology for various purposes. This training is expected to enhance the students' capabilities and motivate them to continue exploring technology in their future endeavors. Keywords: Running Text, Community Service, Technology Training, Junior High School, Skill Development.